Cystic meningioma masquerading as a metastatic tumor: A case report - Ramanathan, Nithya; Kamaruddin, Khairul Azmi; Othman, Aizzat; Mustafa, Fadhli; Awang, Mohamed Saufi (Universiti Sains Malaysia, 2016)
Cystic meningioma is a rare form of intracranial meningioma. Meningiomas are typically solid tumors but may rarely have cystic components. The diagnosis of cystic meningioma is clinically challenging as the finding of multiple intra-axial tumors, including metastatic tumors, is relatively common. We report a case of cystic meningioma initially diagnosed as a metastatic tumor from a recurrence of acute lymphoid leukemia. However, postoperative histopathological examination demonstrated an atypical meningioma.